Competitive Intelligence and Academic Entrepreneurship as Innovative Vectors of a Resilient, Business-Oriented Education - Dinu, Daniel Gabriel; Stoian Karadeli, Andreea; Mihoreanu, Larisa; Pașcu Gabără, Elena Iuliana; Păduraru, Mihail (Journal of Economic Development, Environment and People, 2022)
Purpose – The present paper substantiates that the concepts of competitive intelligence and academic entrepreneurship are genuinely connected to the modern society and, through their perpetual and versatile evolution, have an important role in moving the development on the right way. Design/methodology/approach – Their evolutive is completed by a comparative analysis as appropriate method to point out similarities and differences and identify the way their application may serve innovation as a tool for those activating in the related domains of education, within our highly dynamic world. Findings – The development of the concepts is meant to link and accelerate the technological and operational innovation to a highly competitive academic environment, business-oriented, as a contribution to its wide potential for profit. Originality/value – The correlation between the two concepts provides an innovative tool able to serve as a platform helping the competitive intelligence, as design and functions, for any academic entrepreneurship business-oriented.